The Peruvian beer industry, 1986-1990: an application of Industrial Organization theory - Carrillo Mora, Carlos (1994)
This article tries to define the particular market structure for the Peruvian beer industry between 1986 and 1990, using the theory of industrial organization. This theory takes into account a set of more realistic assumptions to explain the market structure than these models analyzed by classic microeconomics, such as the absence of perfect information, transaction costs, market share and barriers to entry. The application of this theory will allow us to conclude that the oligopoly model is an efficient market structure for the national beer industry.